2022
DOI: 10.3389/fvets.2022.906084
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Heat Stress on Rabbit Immune Function, Endocrine, Blood Biochemical Changes, Antioxidant Capacity and Production Performance, and the Potential Mitigation Strategies of Nutritional Intervention

Abstract: Heat stress has become a widespread concern in the world, which is one of the major environmental stressors and causes substantial economic loss in the rabbit industry. Heat stress leads to multiple damages to the health of rabbits, such as organ damage, oxidative stress, disordered endocrine regulation, suppressed immune function and reproductive disorders, ultimately, induces the decreased production performance and increased mortality. Nutritional approaches, including feeding strategies, adjusting feed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 134 publications
(118 reference statements)
1
19
0
1
Order By: Relevance
“…Environmental stressors in the rabbit industry lead to a deterioration in rabbits’ health, e.g., organ damage, oxidative stress, disordered endocrine regulation, suppressed immune function and reproductive disorders, which cause decreased production performance [ 31 ]. Analysis of morphological and biochemical parameters of blood is an important part of assessing the physiological, nutritional and pathological status of an animal.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental stressors in the rabbit industry lead to a deterioration in rabbits’ health, e.g., organ damage, oxidative stress, disordered endocrine regulation, suppressed immune function and reproductive disorders, which cause decreased production performance [ 31 ]. Analysis of morphological and biochemical parameters of blood is an important part of assessing the physiological, nutritional and pathological status of an animal.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, other studies have found a lower FCR in rabbits raised in heat stress conditions leading to higher feed efficiency. Ondruska et al, 2011;Terhes et al, 2018;Matics et al, 2021) The failure in the zootechnical performance of rabbits subjected to thermal stress is probably due to the reduction in feed intake (Ali and Abdel-Wareth, 2014;Liang et al, 2022). A decrease in feed consumption is a common reaction to heat stress conditions (Ali and Abdel-Wareth, 2014;Okab et al, 2008).…”
Section: Growth Performancementioning
confidence: 99%
“…J., 12 (4): 405-417. DOI: https://dx.doi.org/10.54203/scil.2022.wvj51 reactions affect rabbits by disrupting their physiological functions and behavioral performance (El Sabry et al, 2021;Mutwedu et al, 2021;Liang et al, 2022), such as impairment of appetite, alteration of the feed efficiency and growth performance, milk yield, and reproduction in rabbits, leading to considerable production and economic losses (Plá et al, 1994;Zeferino et al, 2011). It was reported that a reduction of body temperature to 1°C or less suppresses both physiological and growth performance in livestock (Manca et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This change in atmospheric temperature will generate heat stress conditions in tropical and subtropical regions like the south of the Mediterranean, especially in the open production system, which is the most common farm type in Egypt ( 4 ). Rabbit is sensitive to high environmental temperatures and has a low capacity to cope with high ambient temperatures ( 5 ), which negatively affect health, behavior, physiology, reproduction, welfare, meat quality, and production performance of rabbits ( 6 , 7 ). Therefore, heat stress is associated with economic losses to the rabbit industry.…”
Section: Introductionmentioning
confidence: 99%
“…In rabbits, reproductive performance of does is important, and litter traits are the most important traits, which affect the economic benefits of rabbit production that provide the needed animal protein with low capital outlay and time ( 7 ). In this way, Cartuche et al ( 19 ) reported that feed conversion rate during the fattening period, litter size, weaning survival, fattening survival and daily gain during the fattening period are the most economic traits in rabbits.…”
Section: Introductionmentioning
confidence: 99%